Optimizing the Parameters of Zirconium Carbide and Rice Husk Ash Reinforced with AA 2618 Composites. (21st September 2022) - Mahesha, C. R.; Suprabha, R.; Thenmozhi, S.; Gowri, V.; Chowdary, Chirumamill Mallika; Savithiri, V.; Kala Bharathi, B. V. V. L.; Subbiah, Ram; Komalnu Raghavan, Ishwarya
Abstract : Stir casting was utilized to generate the composites. The AA 2618–10wt% zirconium carbide 10wt% rice husk ash hybrid composite had the highest hardness value. In comparison to pure AA 2618, it had a 72% increase. The rule of mixture was used to compute theoretical density, whereas the Archimedes rule was utilized to evaluate real density. For AA 2618, AA 2618/zirconium carbide, and rice husk ash hybrid composites, simple carbide inserts were used for turning. Surface roughness, metal removal rate, and tool wear were among the numerous responses examined. RSM was utilized to analyze and optimize the test outcomes. Feed rate was the most critical issue for surface roughness and material removal rate. Tool wear was shown to be most strongly controlled by tool speed, whereas metal removal rate was found to be least significantly influenced by the weight percent of reinforcement.